2017
DOI: 10.1155/2017/6202783
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine, Chemokine, and Growth Factor Profile Characterization of Undifferentiated and Osteoinduced Human Adipose-Derived Stem Cells

Abstract: Bone is the second most manipulated tissue after blood. Adipose-derived stem cells (ASCs) may become a convenient source of MSC for bone regenerative protocols. Surprisingly, little is known about the most significant biomolecules these cells produce and release after being osteoinduced. Therefore, the present study aimed at dosing 13 candidates chosen among the most representative cytokines, chemokines, and growth factors within the conditioned media of osteodifferentiated and undifferentiated ASCs. Two ackno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
32
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 60 publications
2
32
0
2
Order By: Relevance
“…Several cytokines were detected by Mussano and colleagues in a MSCs culture medium. These included IL-2, IL-6, IL-8, IL10, IL-12, G-CSF, INF-γ, TNF-α, MCP-1 (CCL-2), IP-10, PDGF, bFGF, and VEGF [33]. The authors reported that MSCs produced high levels of IL-6, IL-8, MCP-1 (CCL-2), and VEGF [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several cytokines were detected by Mussano and colleagues in a MSCs culture medium. These included IL-2, IL-6, IL-8, IL10, IL-12, G-CSF, INF-γ, TNF-α, MCP-1 (CCL-2), IP-10, PDGF, bFGF, and VEGF [33]. The authors reported that MSCs produced high levels of IL-6, IL-8, MCP-1 (CCL-2), and VEGF [33].…”
Section: Discussionmentioning
confidence: 99%
“…These included IL-2, IL-6, IL-8, IL10, IL-12, G-CSF, INF-γ, TNF-α, MCP-1 (CCL-2), IP-10, PDGF, bFGF, and VEGF [33]. The authors reported that MSCs produced high levels of IL-6, IL-8, MCP-1 (CCL-2), and VEGF [33]. Schinkothe and colleagues reported that human MSCs produced high levels of G-CSF, IL-12p40, IL-17, CCL2, CCL3, and CCL4 [34].…”
Section: Discussionmentioning
confidence: 99%
“…Both the soluble and the vesicular fractions may act on distinct damaged cells of the nervous system, promoting their survival, angiogenesis, neurite outgrowth, and immunomodulation. This information is based on the articles[85,86].…”
mentioning
confidence: 99%
“…in MSCs culture medium. These included IL-2, IL-6, IL-8, IL10, IL-12, G-CSF, INF-γ, TNF-α, MCP-1 (CCL-2), IP-10, PDGF, bFGF and VEGF [24]. The authors reported that MSCs produced high levels of IL-6, IL-8, MCP-1 (CCL-2) and VEGF [24].…”
Section: Discussionmentioning
confidence: 99%
“…These included IL-2, IL-6, IL-8, IL10, IL-12, G-CSF, INF-γ, TNF-α, MCP-1 (CCL-2), IP-10, PDGF, bFGF and VEGF [24]. The authors reported that MSCs produced high levels of IL-6, IL-8, MCP-1 (CCL-2) and VEGF [24]. Schinkothe and colleagues reported that human MSCs produced high level of G-CSF, IL-12p40, IL-17, CCL2, CCL3 and CCL4 [25].…”
Section: Discussionmentioning
confidence: 99%